Prolonged Survival in a Non-Small Cell Lung Cancer with Brain Metastasis Treated with a Brain Mass Evacuation and Gefi tinib - Mardiah Suci Hardianti; Johan Kurnianda (Acta Interna The Journal of Internal Medicine, 2015)
The incidence of brain metastasis (BM) is reported to be increase about 20-40% over the last few years in patients with non-small-cell lung cancer (NSCLC).1 The use of epidermal growth factor receptor (EGFR) tyrosine kinase inhibitor (TKI) in NSCLC patients with BM, especially those harboring EGFR mutations have been reported.